Interfirm network positioning and firm performance during the mature stage of the global semiconductor industry - Kim, Seong-Young; Kim, Phillip (Management international / International Management / Gestiòn Internacional, 2025)
We study how and why firms shift their interfirm network positions during the routinized regime of a mature high-technology industry. Firms seek benefits from network positions (structural holes or centrality) by forming alliances that move them into these positions and increase their innovation performance. However, during the routinized technology regime, inertia impedes such movements, leading firms a dilemma: whether to continue shifting between two network positions and determine if such shifts yield better outcomes. We analyzed firm network positioning behavior in the semiconductor industry from 1991-2007. Our findings indicate that firms shift toward more central positions, which, in turn, improves innovation performance. These results explain how firms actively shape their network strategy when external conditions discourage such shifts.